Pengaruh Citra Merek, Persepsi Harga dan Kualitas Produk Terhadap Minat Beli Pelanggan - Yosua Prawira (Universitas Tarumanagara, 2019)
The purpose of this study is to find out 1) whether there is an effect of brend image on purchase intention. 2) whether there is an effect of perceive price on purchase intention. 3) whether there is a product quality effect on purchase intention. The population in this study were potential customers and existing customers of automotive brand in Jakarta. The sample used in this study was 180 respondents. The sampling technique used was nonprobability sample with convenience sampling method. Overall the results of this study are 1) Brand image has a positive effect on purchase intention, 2) Perceive price has a positive effect on purchase intention, 3) Product quality has a positive effect on purchase intention.